ANALYSIS OF PERFORMANCE ASSESSMENT, REWARDS AND PENALTIES ON EMPLOYEE PERFORMANCE AT PT. LUAS LINE, SURABAYA - Catur Mei Wulandari; Titin Titin; Deddi Nordiawan (Sean Institute, 2022)
The results of the analysis in this study were carried out by distributing questionnaires or questionnaires directly, then partial and simultaneous tests were carried out using SPSS Version 26. The partial test had resulted in tcount having a value greater than the ttable value (X1 = 3,427>2,011, X2 = 5,129>2,011, X3= 3.116>2.011). So it is known that Performance Appraisal, Reward and Punishment partially affect Employee Performance. For the simultaneous test, Fcount has a value greater than the Ftable value (30,487>2.81). So that the three variables simultaneously affect Employee Performance at PT. Luas Line. And based on the overall dominant test, the most dominant variable on the dependent variable is Reward because it shows that Reward has the highest value, namely 5.129.